The Role Of The Innovative Product In Enhancing Customer Loyalty (A Field Study Of Customers Of Private Insurance Companies Operating In Lattakia) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The innovative product presents a modern and advanced state that most organizations seek to adopt in light of the developments occurring in the business sector and companies in the service sectors, which may contribute to raising levels of loyalty among customers, by reaching high levels of satisfaction with the products provided, which are characterized by their diversity and modernity. It is compatible with the development of their tastes, by offering new products, or working to improve existing products. A descriptive and analytical approach was adopted to complete this study. The questionnaire was distributed to 340 customers from the targeted individuals. The results were summarized that the opinions were average among the sample members regarding the reality of offering a product. New, and also in terms of their evaluation of improving existing products, but in a way that is considered better than the previous ones. The evaluations were also at weak levels with regard to customer loyalty, and that the process of introducing a new product has a moderate effect on enhancing loyalty among customers, and the process of improving an existing product has a moderate effect on It did well in enhancing the loyalty of the research sample members, and a set of recommendations were presented which focused on focusing attention on innovation in general, working seriously to provide new and innovative products, and working seriously to follow market developments to improve as much as possible of the current products, which It enables business organizations to attract a new segment of customers and encourage them with new and developed products that are appropriate to their circumstances and needs, with the aim of achieving their satisfaction and satisfying their needs, which contributes to converting them into permanent customers who feel loyal to their company and the services provided.